2017
DOI: 10.3329/bhj.v32i1.34164
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Tpeak-to-end/QT ratio with Malignant Ventricular Arrhythmias in Acute Anterior ST-Segment Elevation Myocardial Infarction

Abstract: Background: Increased Tpeak-to-end/QT ratio on 12 lead surface electrocardiogram (ECG) has been shown to be the predictor of arrhythmogenesis in various cardiac disorders. There is limited data regarding association of these two parameters with malignant ventricular arrhythmias (MVA) in acute ST-segment elevation myocardial infarction (STEMI) patients. Objectives: This study was conducted to evaluate association of increased Tpeak-to-end/QT ratio with MVAs in acute anterior STEMI. Methods: 178 patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Reza et al (9) found that the average ratio of Tp-e to QT in group 1 was 0.196 ±0.029, while in group 2 it was 0.309 ±0.053. The Tp-e/QT ratio differed significantly among the 2 groups.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Reza et al (9) found that the average ratio of Tp-e to QT in group 1 was 0.196 ±0.029, while in group 2 it was 0.309 ±0.053. The Tp-e/QT ratio differed significantly among the 2 groups.…”
Section: Discussionmentioning
confidence: 97%
“…Reza et al (9) found that the Tp-e/QT ratio, with an odds ratio (OR) of 3.845, was found to be the independently significant predictors of malignant ventricular arrhythmia in a multivariate logistic regression analysis of risk variables for this condition.…”
Section: Discussionmentioning
confidence: 99%